Some comments on the contractual exceptions regulated in the 1984 Civil Code - Ortega Piana, Marco Antonio (2025)
Contracts are an expression of the negotiating power that corresponds to private autonomy and constitute a voluntary distribution of risks, among them, the lack of performance; accordingly, if such situation materializes or is likely to materialize, within the framework of the so-called synallagmatic contracts, the law regulates two self-protection mechanisms that can be used to prevent the loss of the performance parallelism, which will be applicable according to whether the respective business is of simultaneous performance or of successive performance. Consequently, it is necessary to analyze the content, scope, requirements, validity and modalities, if applicable, of each of these means of defense in which it is intendedthat the contractual performance is exceptionally suspended until the state of affairs can be restored normally. Likewise, it is necessary to critically evaluate whether the normative regulation is insufficient or deficient, in order to determine whether its reform is justifie.